Simulation of continuous low pH viral inactivation inside a coiled flow inverter. Issue 4 (17th January 2020) - David, Laura; Bayer, Maximilian P.; Lobedann, Martin; Schembecker, Gerhard
Abstract: Continuous production of monoclonal antibodies is gaining more and more importance. To ensure continuous flow through the entire process as well as viral safety, continuous viral clearance needs to be investigated as well. This study focuses on low pH viral inactivation inside a coiled flow inverter (CFI). Computational fluid dynamics (CFD) simulation is used to gain further insight into the inactivation process inside the apparatus. The influence of viruses in comparison to different tracer elements on the residence time distribution (RTD) behavior is investigated. Finally, the viral inactivation kinetics are implemented into the CFD simulation and real process conditions are simulated. These are compared to experimental results. To the authors' knowledge, this study represents the first successful simulation of continuous viral inactivation inside a CFI. It allows the detailed analysis of processes inside the apparatus and the prediction of experimental virus study results and will therefore contribute to the effective planning of future validation studies. Abstract : To the authors' knowledge, this work represents the first successful simulation of continuous viral inactivation inside a CFI. It allows the detailed analysis of processes inside the apparatus and the prediction of experimental virus study results and will therefore contribute to the effective planning of future validation studies.